Litter decomposing fungi in sal (Shorea robusta) forests of central India - KRISHNA KANT SONI; ABHISHEK PYASI; RAM KEERTI VERMA (Smujo International, 2011)
Abstract. Soni KK, Pyasi A, Verma RK. 2011. Litter decomposing fungi in sal (Shorea robusta) forests of central India. Nusantara Bioscience 3: 136-144. The present study aim on isolation and identification of fungi associated with decomposition of litter of sal forest in central India. Season-wise successional changes in litter mycoflora were determined for four main seasons of the year namely, March-May, June-August, September-November and December-February. Fungi like Aspergillus flavus, A. niger and Rhizopus stolonifer were associated with litter decomposition throughout the year, while Aspergillus fumigatus, Cladosporium cladosporioides, C. oxysporum, Curvularia indica, and C. lunata were recorded in three seasons. Some fungi including ectomycorrhiza forming occur only in the rainy season (June-August) these are Astraeus hygrometricus, Boletus fallax, Calvatia elata, Colletotrichum dematium, Corticium rolfsii, Mycena roseus, Periconia minutissima, Russula emetica, Scleroderma bovista, S. geaster, S. verrucosum, Scopulariopsis alba and four sterile fungi. Fungi like Alternaria citri, Gleocladium virens, Helicosporium phragmitis, and Pithomyces chartarum were rarely recorded only in one season.